2019
DOI: 10.1299/jamdsm.2019jamdsm0048
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing of influencing factors on dynamic response characteristics of double closed-loop control digital hydraulic cylinder

Abstract: A digital hydraulic cylinder that uses mechanical closed-loop feedback regulation to realize double closed-loop control of displacement and velocity is designed in this study. Based on the working principle, the transfer function model and AMESim simulation model of digital hydraulic cylinder were established. The influence of pre-opening distance of the four-way reversing valve, ball-screw lead, inner diameter, and load on the displacement error, adjustment time, overshoot was analyzed. The standard regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The reaching law is consistent with the previously used exponential reaching law based on the hyperbolic tangent function, based on the combined Equations ( 35), (39) and (40). The expression of the sliding mode synchronous controller of the hydraulic cylinder 2 is…”
Section: Synchronous Controller Designsupporting
confidence: 73%
See 1 more Smart Citation
“…The reaching law is consistent with the previously used exponential reaching law based on the hyperbolic tangent function, based on the combined Equations ( 35), (39) and (40). The expression of the sliding mode synchronous controller of the hydraulic cylinder 2 is…”
Section: Synchronous Controller Designsupporting
confidence: 73%
“…The aforementioned study indicates that the use of closed-loop control is often employed inside hydraulic synchronization control systems to enhance the precision of those systems. The synchronization precision and stability of the hydraulic synchronous control system may be greatly increased by the controller by outputting the signal adjustment amount to compensate for the hydraulic system's synchronization error [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…However, the information contained in the 350 feature parameters collected for each tool path may not be directly related to tool wear or may exhibit weak correlations. Therefore, this study employs the Pearson correlation coefficient method (Xia et al, 2019) to conduct preliminary feature selection. This helps reduce unnecessary computational burden and improves the convergence speed of the model.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Hydraulic systems are typically classified into either open-loop or closed-loop circuits. Studies on valve-controlled open-loop systems have shown problems of pressure drops and leakages at control valves, resulting in energy wastage [1][2][3]. On the other hand, closed-loop circuits offer increased transmission efficiency by eliminating the need for directional control valves.…”
Section: Introductionmentioning
confidence: 99%